RNA degradation patterns in cardiac tissues kept at different time intervals and temperatures before RNA sequencing - Stine Bøttcher Jacobsen; Jacob Tfelt-Hansen; Morten Holdgaard Smerup; Niels Morling; Jeppe Dyrberg Andersen (PLoS ONE, 2025)
Vast repositories of tissues are available in biobanks worldwide. For these tissues to be used for molecular investigations, such as gene expression analysis, it is important to understand the limitations of pre-analytical variables. Storage times and temperature may influence the integrity of the tissue and thereby affect the results of gene expression analyses. To evaluate the effect of storage time at different temperatures, we performed whole transcriptome sequencing of human right atrial appendage tissues stored at either 4°C or 22°C for zero, one, seven, 14, or 28 days. We observed a temperature-dependent RNA degradation with time, as RNA was more stable at 4°C than 22°C. We found that nuclear protein-coding RNAs appear to degrade faster than RNAs encoded by the mitochondrial genome. The global gene expression profiles were relatively stable for up to 24 hours. However, more than seven days of storage induced widespread changes in the gene expression profiles. These changes may, though, be counteracted by including the RNA integrity number as a covariate in the differential expression analyses. We recommend storing tissues at temperatures below 4°C or limiting storage time at temperatures above 4°C in order to produce reliable gene expression profiles.